Infrastructure and economic growth - Markus Brückner (Journal of Risk and Financial Management, 2021)
I estimate the effect that growth in countries' GDP per capita has on the growth rate of infrastructure. In order to extract exogenous variation in GDP per capita growth, I use the growth of the international oil price multiplied with countries' GDP shares of oil net-exports as an instrumental variable. My instrumental variables estimates show that, for both democracies and autocracies, GDP per capita growth has a significant positive effect on infrastructure growth. This effect is significantly smaller in anocracies-so much so that, in anocracies, GDP per capita growth has no significant effect on the growth rate of infrastructure.
Keywords: H05; P01; 330; anocracy; economic growth; infrastructure